2008
DOI: 10.1161/circheartfailure.107.736975
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Baseline and Changes in Systolic Blood Pressure Over Time on the Effectiveness of Valsartan in the Valsartan Heart Failure Trial

Abstract: Background-Low systolic blood pressure (SBP) is a risk factor for adverse outcomes in patients with heart failure (HF).Valsartan improved morbidity rates in the Valsartan Heart Failure Trial (Val-HeFT) despite a reduction in SBP. The aim of the present study was to investigate the relationship between the SBP-lowering effects of valsartan and its cardiovascular protective effects in this population. Methods and Results-Baseline measurements and changes in SBP at 4 months were related to mortality and morbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 27 publications
4
26
0
1
Order By: Relevance
“…These findings may be somewhat analogous to effect of valsartan on blood pressure as seen in Val-HeFT (35 …”
Section: Discussionsupporting
confidence: 67%
“…These findings may be somewhat analogous to effect of valsartan on blood pressure as seen in Val-HeFT (35 …”
Section: Discussionsupporting
confidence: 67%
“…suggested that the clinical benefits of add‐on neurohormonal blockade may be balanced or even neutralized by risk for hypotension . However, reports from large HF trials, such as COPERNICUS, CHARM, A‐HeFT and Val‐HeFT, suggest that dosing and trial completion are limited to a greater extent by the severity of HF than by drug intolerance to HF therapy per se , as patients receiving placebo were almost as likely to discontinue as patients receiving the active study treatment, regardless of SBP. Furthermore, in line with these and more recent trial data, practical guidance for the management of HF patients with low SBP emphasizes the importance of using guideline‐directed therapies despite low SBP as the symptoms of hypotension may resolve as HF improves …”
Section: Discussionmentioning
confidence: 99%
“…However, the beneficial effects of the HF medications are usually independent of the baseline BP or changes in BP and do not vary according to baseline BP or reductions in SBP levels. [60][61][62] Medication Choices for the Treatment of Hypertension in Patients With HF Currently, there are no randomized, large-scale trials comparing the effectiveness of different antihypertensive medications targeting optimal treatment of BP solely in patients with hypertension and established HF. Thus, most evidence comes from hypertension clinical trials that have not excluded patients with a history of HF.…”
Section: Iia C 8 71mentioning
confidence: 99%